Towards higher energy efficiency in future waste-to-energy plants with novel latent heat storage-based thermal buffer system. (September 2019) - Xu, H.; Lin, W.Y.; Dal Magro, F.; Li, T; Py, X.; Romagnoli, A.
Abstract: Energy efficiency of current Waste-to-Energy plants is mainly limited by high temperature corrosion combined with temperature fluctuation of flue gas. This paper introduces a technology based on Phase Change Materials in the combustion chamber and its contribution to higher overall electrical efficiency. This technology encapsulates aluminium alloy-based Phase Change Materials in ceramic bricks similar to traditional refractory bricks in the combustion chamber. The proposed brick allows steam superheating on waterwall by absorbing temperature fluctuations and delivering a higher heat flux. Two studies are carried out to realize the technology development from refractory bricks to waterwall system. Study One adopts Dynamic Thermal Network method to model the heat transfer on waterwall with and without the novel brick. Real plant information is used as boundary condition to locate the design points of the novel bricks. Study Two conducts experiment to validate the numerical model, and performs a transient analysis of the waterwall to compare the thermal dampening and superheating effect of Phase Change Material-based waterwall. From the result, there is a 10% improvement in energy conversion efficiency on the waterwall by introducing the novel technology. Lastly, this paper introduces an integration scheme of three types of Phase Change Materials-based bricks in the waterwall to achieve continuous superheating of steam. A 34% electrical efficiency can be achieved by producing over 600 °C of superheated steam with this new plant configuration. The result shows that this new technology is highly applicable and promising to upgrade the overall efficiency of Waste-to-Energy plants. Highlights: Latent heat-based brick is proposed to buffer temperature fluctuation in waterwall. Thermal network model is used to study the transient response of the new brick. Experimental result is employed to validate the numerical model in system level. Technology integration of new brick-based waterwall to Waste-to-Energy plant proposed. High steam parameter over 600 °C can be achieved with proposed plant configuration.